The exploitations of medieval romance - Ashe, Laura; Djordjević, Ivana; Weiss, Judith (Boydell & Brewer, 2010)
As one of the most important, influential and capacious genres of the middle ages, the romance was exploited for a variety of social and cultural reasons: to celebrate and justify war and conflict, chivalric ideologies, and national, local and regional identities; to rationalize contemporary power structures, and identify the present with the legendary past; to align individual desires and aspirations with social virtues. But the romance in turn exploited available figures of value, appropriating the tropes and strategies of religious and historical writing, and cannibalizing and recreating its own materials for heightened ideological effect. The essays in this volume consider individual romances, groups of writings and the genre more widely, elucidating a variety of exploitative manoeuvres in terms of text, context, and intertext. Contributors: Neil Cartlidge, Ivana Djordjevic, Judith Weiss, Melissa Furrow, Rosalind Field, Diane Vincent, Corinne Saunders, Arlyn Diamond, Anna Caughey, Laura Ashe